2018
DOI: 10.1088/1361-6528/aac7a3
|View full text |Cite
|
Sign up to set email alerts
|

High-speed large area atomic force microscopy using a quartz resonator

Abstract: A high-speed atomic force microscope for scanning large areas, utilizing a quartz bar driven close to resonance to provide the motion in the fast scan axis is presented. Images up to 170 × 170 μm have been obtained on a polydimethylsiloxane (PDMS) grating in 1 s. This is provided through an average tip-sample velocity of 28 cm s at a line rate of 830 Hz. Scan areas up to 80 × 80 μm have been obtained in 0.42 s with a line rate of 1410 Hz. To demonstrate the capability of the scanner the spherulitic crystalliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…However, the sample size is extremely limited due to the size of the tuning fork [21]. To overcome this issue, different designs such as the quartz bar and the piezoelectric bimorph-based scanner were proposed [22]- [25]. The quartz bar scanner developed by Zhao et al achieved a travel range of 37.5 μm at its resonant frequency of 772 Hz [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sample size is extremely limited due to the size of the tuning fork [21]. To overcome this issue, different designs such as the quartz bar and the piezoelectric bimorph-based scanner were proposed [22]- [25]. The quartz bar scanner developed by Zhao et al achieved a travel range of 37.5 μm at its resonant frequency of 772 Hz [22].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al further demonstrated that the travel range and the resonant frequency can be designed through modifying the length of the quartz bar. Through using a long quartz bar with a size of 4 mm × 5.5 mm × 66 mm (thickness × height × length), a large travel range of 170 μm was achieved at its resonant frequency of 830 Hz [25]. Both the quartz bar and bimorph-based scanners utilize the first resonant mode of the cantilever beam structure to magnify the travel range.…”
Section: Introductionmentioning
confidence: 99%
“…High-speed AFM scanners have been developed by using piezoelectric actuators with ultrahigh resonant frequency [100,102], however, the imaging speed increase was achieved by sacrificing the scan range by at least 80% compared to normal AFM scanners and the hardware modification cost was significant. Although it has been tried to overcome this limit [103,104] by using piezoelectric actuator with ultra-high resonant frequency and the tip velocity could reach as fast as 28cm/s, such a speed improvement is associated to extra hardware cost. More importantly, the imaging force cannot be effectively controlled.…”
Section: Experiments Resultsmentioning
confidence: 99%